AUTOREGLAREA ÎNVĂŢĂRII ŞI EFICIENŢA ACADEMICĂ ÎN CONTEXTUL UNIVERSITAR - USM ADMIN (Moldova State University, 2007)
Self-regulated learning (SRL) has become a current focus for research, and one of the essential axes of educational practice. Taking of current publications in the filed as our reference, this paper's objective is to examine the main points of learning and of the concept self-regulated learning related to the characteristics differentiated students high self-regulating, and the relationships between SRL and academic performance in the university context. A review of relevant research revealed that: learning is an active, cognitive, constructive, significant, mediated and self-regulated process; the characteristics attributed to self-regulating persons coincide with those attributed to high-performance, high capacity students. However, SRL is not a characteristic that is genetically based or formed early in life so those students are "stuck" with it for the rest of their lives, SRL can be thought, learned and controlled.